"Eat, pray, love. Ritalin": A qualitative investigation into the perceived barriers and enablers to parents of children with ADHD undertaking a mindful parenting intervention. (November 2019) - Ruuskanen, Ella; Leitch, Sophie; Sciberras, Emma; Evans, Subhadra
Abstract: Background and purpose: There is growing interest in how mindful parenting interventions (MPI) may support families of children with attention deficit hyperactivity disorder (ADHD). The aim of this study was to explore the potential barriers and enablers to parents' participation in a MPI from the perspectives of parents of children with ADHD and healthcare providers. Materials and methods: Thirteen parents of children with ADHD attended focus groups, and seven healthcare providers participated in semi-structured phone interviews. Transcripts of the focus groups and interviews were analysed using inductive thematic analysis. Results: Three overarching themes related to potential barriers and enablers were identified: parent motivation and capacity to engage in a MPI, the need for multimodal and personalised delivery, and considerations for real-world program implementation. Conclusion: Parents of children with ADHD appear to require flexible, multimodal MPIs that consider parents' emotional experiences, priorities, and personal struggles. Highlights: Parents of children with ADHD and healthcare providers reported on barriers and enablers to parents undertaking mindful parenting. Themes included parent motivation and capacity, multimodal delivery, and consideration for parent demands. To increase feasibility and acceptability, programs should be designed with parent needs and challenges in mind.